Pengaruh Komunikasi Pemasaran Terintegrasi (Integrated Marketing Communication) Terhadap Ekuitas Merek Melalui Kesadaran Merek Pada UMKM Unggulan Kota Tasikmalaya - Nugraha, Jeffry; Sudianto, Sudianto (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
The sustainability of the business sector is strongly supported by Micro, Small, and Medium Enterprises (MSMEs). As information technology continues to evolve, marketing communication strategies are increasingly needed to enhance brand strength amid digital competition. Integrated Marketing Communication (IMC) is one approach frequently applied, integrating multiple communication media so that consumers receive messages in a uniform manner. At present, IMC encompasses both conventional and digital channels to adapt to changing consumer behavior. This study seeks to analyze how digital marketing communication, within the IMC perspective, impacts brand awareness and brand equity of superior MSME products in Tasikmalaya City. Tasikmalaya City is home to nine categories of superior products. The findings reveal that although most MSMEs have adopted digital tools like Shopee, Instagram, and Facebook, challenges remain in maximising their digital marketing practices. Limited human resources dedicated to digital communication management and less appealing content are the core issues faced. This research further confirms that brand awareness significantly contributes to the formation of brand equity. MSMEs such as Yola Bordir, Rumah Kayu Bordir, Batik Agnesa, and Batik Alika managed to raise brand awareness through partnerships and the application of updated strategies. The study concludes that providing training and education is vital for improving MSMEs’ competencies in digital marketing communication. A strategy-driven approach is seen as effective in safeguarding the identity of local products from Tasikmalaya while simultaneously broadening their market opportunities.
Keywords: Digital Marketing Communication (Integrated Marketing Communication); Brand Awareness; Brand Equity; Msmes; Superior Products; Innovation; Tasikmalaya